Biochemical studies on muscarinic cholinergic receptors - Carson, S (1982)
A novel solubilising agent (0.l% sodium cholate—lM NaCl) has been developed which will solubilise 10—30% of muscarinic cholinergic receptors from bovine caudate nucleus. Using the muscarinic antagonist quinuclidinyl benzilate (QNB), a single saturable binding component was found with an equilibrium constant of ZOOpM, approximately 10—fold higher than the membrane receptor and 4—fold higher than the ratio k-l/kl determined kinetically in the soluble material. This latter difference may indicate that the binding of QNB to the solubilised receptor is not a simple second—order process. Inhibition constants for a variety of muscarinic agonists and antagonists were 10 to 20—fold higher than in the membrane state and non-muscarinic ligands were without effect. The decrease in affinity was shown to be due to the presence of high salt. Evidence was presented that the apparent increase in Hill coefficient for muscarinic agonist binding to soluble material was not due to a differential solubilisation of muscarinic receptors or to a conformational change of high to low affinity agonist sites during the solubilisation. Instead the Hill coefficient of the soluble material decreased as the percentage of total binding sites solubilised increased. The stability of receptor binding at different temperatures was shown to be dependent on the protein: cholate (w/w) ratio. Results from gel filtration, affinity chromotography and immunization studies are also reported. The results of this thesis are discussed in the light of the possible importance of phospholipids for receptor activity.